Rethinking Women’s Empowerment: Insights from the Russian Arctic - Marya S. Rozanova; Valeriy L. Mikheev (Social Sciences, 2020)
This article examines women’s political empowerment in the Russian Arctic as an example of progress towards gender equality. In contrast to women’s severe underrepresentation in Russian federal politics, a strong trend towards women’s political empowerment can be observed in the Arctic regions of the country. Using the Nenets Autonomous Region as a case study, this article is aimed at narrowing the research gaps in women’s leadership by examining the representation of female deputies in both the regional and local levels of government/self-government. Research on women’s numerical representation indicates that women’s participation and political empowerment in decision-making processes are manifested most vividly in predominantly indigenous communities. Placing a special focus on these Arctic communities, this study describes the historical and institutional roots that impact shifts in traditional gender role and contribute to a phenomenon of indigenous women’s empowerment. Along with this positive pattern of women’s leadership, this study also reveals an alarming trend of “reverse gender disparity” concerning men’s severe underrepresentation in positions of power in indigenous communities of the North. The study results suggest that to achieve gender equality, a holistic approach to women’s empowerment requires taking into account socio-cultural and historical contexts, as well as regional and territorial disparities.